Balancing justice goals: restorative justice practitioners' views. Issue 4 (1st October 2016) - Crocker, Diane
Abstract: Despite the importance of facilitators, staff, and volunteers to restorative justice programs, we know very little about what they think about the goals of restorative justice. This paper fills that gap by reporting the findings of a survey of restorative justice practitioners in Nova Scotia, Canada. Participants rated the importance of 29 justice-related goals such as punishment and accountability. The results show how respondents distinguish between, prioritize, and balance competing justice goals. A factor analysis shows how goals cluster together revealing more depth about how practitioners understand goals, such as accountability, that have different meanings depending on the context. The findings are particularly interesting because the restorative justice program in Nova Scotia is deeply embedded in the criminal justice system. The findings speak to concerns about whether programs rooted in the mainstream system risk being diluted by dominant criminal justice system discourses. I conclude that restorative justice practitioners can prioritize the values of restorative justice in a program that is deeply rooted in the mainstream criminal justice system.